Sleep Bruxism and Occurrence of Temporomandibular Disorders-Related Pain: A Polysomnographic Study - Smardz, Joanna; Martynowicz, Helena; Michalek-Zrabkowska, Monika; Wojakowska, Anna; Mazur, Grzegorz; Winocur, Efraim; Wieckiewicz, Mieszko (Frontiers in Neurology, 2019)
Introduction The diagnosis of sleep bruxism is challenging due to the difficulties involved. Sleep bruxism can lead to significant clinical consequences, including pain in masticatory muscles, limitation of jaw mobility, headache, and the spectrum of symptoms associated with damage to the teeth and oral mucosa. Currently, only video-polysomnography can definitely diagnose sleep bruxism. Due to the risk of painful temporomandibular disorders (TMD) in sleep bruxers, early diagnosis of pain in the temporomandibular region using questionnaires is recommended. Therefore, this study aimed to assess the relationship between the intensity of sleep bruxism and the occurrence of pain related to TMD. Materials and methods This study was conducted on the patients of the Clinic of Prosthetic Dentistry operating at the Department of Prosthetic Dentistry at the Wroclaw Medical University. Based on a positive medical history, a thorough examination for the diagnosis of probable sleep bruxism was carried out in the enrolled patients. Eligible patients were then subjected to a video-polysomnographic study. Each patient was asked to complete the TMD Pain Screener questionnaire to assess the occurrence of pain in jaw and temple area. Results The results of the study showed that increased bruxism episode index (BEI) was statistically significantly correlated with increase of all types of bruxism episodes—phasic, tonic, and mixed—in all the studied patients; a significant correlation was also found with respect to division of patients into studied and control groups. The study also showed that there was no statistically significant difference between BEI values and scores of TMD Pain Screener. In all the studied patients, a higher BEI was not found to be correlated with the occurrence of TMD-related pain assessed by TMD Pain Screener; similarly, no correlation was found with respect to division of patients into studied and control groups. Conclusions The occurrence of TMD-related pain is not related to the intensity of sleep bruxism. TMD Pain Screener may be used as an auxiliary tool in the diagnosis or risk of occurrence of TMD-related pain, whereas in the case of sleep bruxism, it has only limited diagnostic value. Trial registration: Clinical Trials NCT03083405, WMU1/2017, https://clinicaltrials.gov/ct2/show/NCT03083405